Enhanced strength and electrical conductivity in pure copper via dynamic offsets and shear force adjustments cryorolling combining annealing - Longfei Xu; Renhao Wu; Shi Woo Lee; Xin Xue; Yan Peng; Yuhui Wang; Hyoung Seop Kim (Materials & Design)
Asymmetric cryorolling demonstrates significant potential for producing materials with high strength and excellent electrical conductivity. This study presents an innovative Dynamic Offsets and Shear Force Adjustments Cryorolling (DSCR) technique coupled with short-time annealing (DSCRA), systematically investigating its synergy in tailoring mechanical properties, microstructural, recrystallization behavior, and thermal stability of pure copper. Compared to conventional symmetric rolling (SR) followed by annealing (SRA), the DSCRA specimens exhibit 27.9% higher microhardness and 18.3% enhanced ultimate tensile strength under annealing at 180 °C for 15 min, primarily driven by optimized dislocation strengthening and grain boundary strengthening. Both SRA and DSCRA specimens achieve >95% IACS electrical conductivity at elevated annealing temperatures. Microstructural analysis reveals that DSCRA specimens generate weaker and more homogeneous texture prior to recrystallization, resulting in 31.3% higher grain growth activation energy and superior thermal stability. These findings establish DSCRA as an industrially scalable strategy for manufacturing high-performance copper plates, providing critical insights for designing deformation-annealing protocols for conductive structural materials.